PENGARUH TEMPERATUR SINTERING KAOLIN PADA BATA TAHAN API TERHADAP UJI DENSITAS, POROSITAS DAN KUAT TEKAN - Ahmiyati, Yusniar; Rajagukguk, Tumpal Ojahan (Bhinneka Multidisiplin Journal, 2026)
Fire bricks possess the ability to withstand high temperatures; however, repeated use beyond their capacity can lead to failure. As construction materials, fire bricks maintain their shape and strength at extremely high temperatures. Kaolin is a natural mineral belonging to the clay group, with kaolinite as its primary constituent. The decomposition of kaolinite into metakaolinite occurs between 400 and 630°C, and metakaolin gradually promotes the formation of mullite crystals. Alumina is one of the most widely used raw materials in refractory applications due to its high heat resistance, as well as its resistance to erosion and corrosion. This study aims to analyze fire bricks produced by sintering kaolin at 700°C, while varying the compositions of kaolin, alumina, and chamotte, followed by firing at 1300°C. Density test results indicate that Sample 3 yielded the best value of 2.14 g/cm³. Porosity test results show that Sample 3 achieved the optimal value of 16.4%. Compressive strength test results demonstrate that Sample 3 produced the highest value of 34.79 N/mm². This research has the potential to serve as an alternative solution for developing fire bricks applicable in the petrochemical industry, iron and steel production, boilers, power plants, ceramics, glass, and other sectors.